Murder, Gender and the Media Narratives of Dangerous Love - Smith, Jane Monckton. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
A shocking look at how the idea of romantic love can justify and excuse the killing of women by their partners, and lead to sympathy and reduced sentences for the killers. The author explores how stories of domestic homicide are told in the news, by the police, and in the courts, drawing from 72 cases which took place over a twelve month period.